User-identified electronic cigarette behavioral strategies and device characteristics for cigarette smoking reduction. (April 2018) - Soule, Eric K.; Maloney, Sarah F.; Guy, Mignonne C.; Eissenberg, Thomas; Fagan, Pebbles
Abstract: Background: There is limited evidence on how cigarette smokers use electronic cigarettes (ECIGs) for smoking cessation and reduction. This study used concept mapping, a participatory mixed-methods research approach, to identify ECIG use behaviors and device characteristics perceived to be associated with cigarette smoking cessation or reduction. Methods: Current ECIG users aged 18–64 were recruited from seven cities selected randomly from U.S. census tract regions. Participants were invited to complete concept mapping tasks: brainstorming, sorting and rating ( n  = 72). During brainstorming, participants generated statements in response to a focus prompt ("A SPECIFIC WAY I HAVE USED electronic cigarettes to reduce my cigarette smoking or a SPECIFIC WAY electronic cigarettes help me reduce my cigarette smoking is…" ) and then sorted and rated the statements. Multidimensional scaling and hierarchical cluster analyses were used to generate a cluster map that was interpreted by the research team. Results: Eight thematic clusters were identified: Convenience, Perceived Health Effects, Ease of Use, Versatility and Variety, Advantages of ECIGs over Cigarettes, Cigarette Substitutability, Reducing Harms to Self and Others, and Social Benefits. Participants generated several statements that related to specific behavioral strategies used when using ECIGs for smoking reduction/complete switching behaviors such as making rapid transitions from smoking to ECIG use or using certain ECIG liquids or devices. Former smokers rated the Perceived Health Effects cluster and several behavioral strategy statements higher than current smokers. Conclusions: These results help to identify ECIG use behaviors and characteristics perceived by ECIG users to aid in cigarette smoking cessation or reduction. Highlights: ECIG users identify many behaviors and device characteristics for smoking reduction. Many ECIG users are unaware of their ECIG device/liquid characteristics. Many smokers who use ECIGs for smoking reduction continue to smoke cigarettes. Switching abruptly from cigarettes to ECIGs may be more associated with smoking reduction.